Pemahaman Dan Implementasi Hadis Tentang Shalat Jum’at Masjid Raya Darul Ma’ruf Batang Kabung Ganting Kota Padang - Arifa'i Saputra; Luqmanul Hakim; Zulfikri Zulfikri (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Friday prayers at the Grand Mosque of Darul Ma'ruf Batang Kabung, Padang City. The implementation of the Friday prayers they perform is different from the usual Friday prayer practices. However, in the implementation of Friday, which is in the mosque, the sermon is in the form of a foreign language (Arabic) which is not the language understood by the local congregation at all. In the implementation of Jum'at jama'ah pray together while waiting for Friday to enter and there are two call to prayer and two preachers in one Friday. The formulation of the problem in this research is how the congregation's understanding of the Great Mosque of Darul Ma'ruf Batang Kabung about the Virtue hadith and Friday prayer practices and how the congregation is implemented at the Great Mosque of Darul Ma'ruf Batang Kabung regarding the Virtue hadith and Friday prayer practices. . The purpose of this study is to determine the understanding of the congregation of the Masjid Raya Darul Ma'ruf Batang Kabung regarding the Virtue hadith and Friday prayer practices and to describe the implementation of the congregation at the Grand Mosque of Darul Ma'ruf Batang Kabung regarding the Virtue hadith and Friday prayer practices. The data sources used are primary and secondary. Observation data collection methods (Observation), interviews, and documentation. After the data has been collected, it is analyzed using a qualitative descriptive method. The results of the study are related to the understanding of the congregation of the Grand Mosque of Darul Ma'ruf about the hadith of the Prophet about the virtue and practice of Friday prayers, they understand that Friday as Friday is a day of forgiveness, Friday is the day of association and Friday. 'at is the greatest almsgiving and sacrifice. As for the implementation of the Friday prayer practice at the Masjid Raya Darul Ma'ruf Batang Kabung, the congregation divides it into three stages, namely the time to wait for Friday prayers, the time for prayer has entered and the prayer time has finished. Suggestions in this study are to revive the recitations, especially the discussion about prayer services and provide a variety of comfortable and peaceful facilities.